PERANCANGAN PERMAINAN (GAME) EDUKASI BELAJAR MEMBACA PADA ANAK PRASEKOLAH BERBASIS SMARTPHONE ANDROID (Studi Kasus : Taman Kanak-Kanak Ikal Iqra Padang Selatan) - Busran; Fitriyah (Jurnal Teknoif Teknik Informatika Institut Teknologi Padang, 2015)
Learning to read is the first step towards a more complex learning process in the development of preschool children, learning to read is a way of voicing the letters into a word and sentence learning process of reading in children should not be done with a formal approach to learn to read using a textbook that should accompanied by parents and teachers but informal approaches such as play while learning also can help facilitate the learning. The application of this tool was designed using the Java programming language is one programming language oriented to objects (Object Oriented Programming / OOP) using supporting software JDK, Eclipse IDE, SDK, ADT can simplify the design of a software application. The use of objects in the design of an application can be used as teaching aids in the form of educational games android-based smartphone with mobile learning technology. With the learning aids for learning to learn to read using mobile learning technology is expected to help preschoolers in the learning process, this application also comes with a sample that is accompanied by audio pronunciations so much easier in understanding